2021
DOI: 10.3390/horticulturae7110508
|View full text |Cite
|
Sign up to set email alerts
|

Flowering Biology of Rhododendron pulchrum

Abstract: To study the flowering biology of Rhododendron pulchrum, we used scanning electron microscopy (SEM) and paraffin sectioning to observe the microstructures of its floral organs, a methyl thiazolyl tetrazolium (MTT) colorimetric assay to detect pollen viability in different periods, continuous observations to study flowering phenology, and artificial pollination and a benzidine-hydrogen peroxide method to determine stigma receptivity. R. pulchrum exhibited a centralized flowering phenology. The protogynous stigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Although the early onset of the stigma receptivity indicates protogyny, it was incomplete, as the male and female phases overlapped considerably over the lifespan of the flower. Occurrence of incomplete protogyny has been shown in R. pulchrum Sweet ( Qiu et al., 2021 ), in contrast to R. semibarbatum Maxim., which exhibits protandry ( Ono et al., 2008 ). The continuous receptivity of the stigma across the floral life-span could be due to the selective pressure to enhance the likelihood of receiving pollen, rather than aiding in pollen dispersal which in turn determines the longevity of flowers as seen in Flame Azalea ( R. calendulaceum (Michx.)…”
Section: Discussionmentioning
confidence: 99%
“…Although the early onset of the stigma receptivity indicates protogyny, it was incomplete, as the male and female phases overlapped considerably over the lifespan of the flower. Occurrence of incomplete protogyny has been shown in R. pulchrum Sweet ( Qiu et al., 2021 ), in contrast to R. semibarbatum Maxim., which exhibits protandry ( Ono et al., 2008 ). The continuous receptivity of the stigma across the floral life-span could be due to the selective pressure to enhance the likelihood of receiving pollen, rather than aiding in pollen dispersal which in turn determines the longevity of flowers as seen in Flame Azalea ( R. calendulaceum (Michx.)…”
Section: Discussionmentioning
confidence: 99%
“…During the single-flower lifespan (approximately 8–10 d), the pollen had high stainability for only a short time, leading to low stamen fitness. Stigma receptivity is an important indicator of flower maturation and affects the transmission rate, self-pollination rate and gametophyte selection at different stages after flowering; furthermore, stigma strength is an important prerequisite for pollination and fertilization 45 . The stigma of C. speciosa can accept pollen even before flowering, which is manifested by the observation that the pistil matured before the stamen.…”
Section: Discussionmentioning
confidence: 99%
“…The most suitable medium for in vitro pollen germination varies by species, or even by different flowering states to collect pollen for the same species. Hemerocallis (Qiu et al, 2021) has the highest percentage of in vitro germination occurred with the concentrations of 4 g L agar, 74.6 g L sucrose, 800 mg L boric acid and 590 mg L calcium nitrate; Passiflora spp. Orthogonal experimental design (OED) is a design method for the study of multi-factor and multi-level systems and can find the optimal level combination through a small number of experiments.…”
Section: Selection Of the Optimal Culture Mediummentioning
confidence: 99%
“…(Batos andMilj ković, 2019) (Beck-Pay, 2012). The most common external factors include incubation time, incubation temperature and storage temperature (Báez et al, 2002;Wang et al, 2021). Many plant biologists and researchers suggested that each species required different growth conditions and culture media.…”
Section: Introductionmentioning
confidence: 99%